Tuning the Intrinsic Properties of Carbon Nitride for High Quantum Yield Photocatalytic Hydrogen Production. Issue 10 (14th August 2018) - Rahman, Mohammad Z.; Davey, Kenneth; Mullins, C. Buddie
Abstract: The low quantum yield of photocatalytic hydrogen production in carbon nitride (CN) has been improved upon via the modulation of both the extrinsic and intrinsic properties of the material. Although the modification of extrinsic properties has been widely investigated in the past, recently there has been growing interest in the alteration of intrinsic properties. Refining the intrinsic properties of CN provides flexibility in controlling the charge transport and selectivity in photoredox reactions, and therefore makes available a pathway toward superior photocatalytic performance. An analysis of recent progress in tuning the intrinsic photophysical properties of CN facilitates an assessment of the goals, achievements, and gaps. This article is intended to serve this purpose. Therefore, selected techniques and mechanisms of the tuning of intrinsic properties of CN are critically discussed here. This article concludes with a recommendation of the issues that need to be considered for the further enhancement in the quantum efficiency of CN photocatalysts. Abstract : Carbon nitride, a metal‐free semiconductor, draws significant interest as a photocatalyst . It is now being widely used for photocatalytic hydrogen production. Pristine carbon nitride is inefficient as a photocatalyst. Therefore, modulation of extrinsic and intrinsic properties are adapted to obtain high quantum efficiency. The new approaches of molecular tuning of the intrinsic properties of carbon nitride are discussed and recommendations for further enhancing the hydrogen quantum yield are provided.